Right first time recruitment skills - White, Paul (London : BBC for Business, 1995)
Right first time provides all the materials required to run a training session on effective interviewing and recruitment
Copy available in DVD format
Editor, Bryan De'ath ; writer, Vicky Pile
Keywords: Employment interviewing